Hydrogeological conditions in the Terai plain of Morang district, eastern Nepal - Bhattarai, T. N.; Rao, G. Krishna (Journal of Nepal Geological Society, 1989)
The Terai Plain of Morang District is underlain by thick alluvium deposits. Alternate sequence of gravel, sand and clay turn into multiaquifer system. Artesian conditions occur in some parts of the middle Terai. The area possesses rich groundwater potential which can be used for industrial and large scale irrigation. Over development of groundwater is suggested to reclaim the land under water-logging and marshy conditions in the middle Terai.